2020 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2020
DOI: 10.1109/vr46266.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Detecting System Errors in Virtual Reality Using EEG Through Error-Related Potentials

Abstract: When persons interact with the environment and experience or witness an error (e.g. an unexpected event), a specific brain pattern, known as error-related potential (ErrP) can be observed in the electroencephalographic signals (EEG). Virtual Reality (VR) technology enables users to interact with computer-generated simulated environments and to provide multi-modal sensory feedback. Using VR systems can, however, be error-prone. In this paper, we investigate the presence of ErrPs when Virtual Reality users face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Holroyd and Coles [7] proposed that an error-processing system in the ACC serves as reinforcement-learning signals to correct errors. Further studies have also shown that error-related potentials (ErrPs) spontaneously arise when users experience BiEs during avatar-based interaction in VR [4,[8][9][10][11][12][13]. These findings support the notion of an accumulation of errors in these conditions [14][15][16], where cognitive processes in embodiment contribute to a global error in user experience.…”
Section: Introductionmentioning
confidence: 55%
“…Holroyd and Coles [7] proposed that an error-processing system in the ACC serves as reinforcement-learning signals to correct errors. Further studies have also shown that error-related potentials (ErrPs) spontaneously arise when users experience BiEs during avatar-based interaction in VR [4,[8][9][10][11][12][13]. These findings support the notion of an accumulation of errors in these conditions [14][15][16], where cognitive processes in embodiment contribute to a global error in user experience.…”
Section: Introductionmentioning
confidence: 55%
“…Unlike subjective measures, neurophysiological measures like the EEG directly reflect changes in cortical brain activity and therefore might provide, compared to subjective reports, a more direct basis for insights into the validity of theoretical frameworks that seek to explain psychophysical effects. It has already been shown that error-related potentials can indeed be detected while wearing an HMD, thus supporting self-adaptive VR environments (Si-Mohammed et al, 2020).…”
Section: Introductionmentioning
confidence: 83%
“…Midline cingulate EEG sources contributed to prediction error ERPs, 'PENs' , and may serve as a robust source to detect violations of user's predictions about the interaction with virtual worlds [7,8,20]. This source origin can be specifically and repeatedly probed for real-time BCI purposes, informing the technical system about the user's mental representation generating the predictions [20,58].…”
Section: Conclusion and Outlook: Towards A Robust Metric Of Presence ...mentioning
confidence: 99%
“…We and others have previously proposed the use of the frontal 'prediction error' negativity (PEN) as a feature for fast, real-time, detection of VR system errors which may, in turn, cause a loss in the sense of physical immersion [7][8][9]. Based on the idea that the brain has evolved to optimize motor behavior by detecting sensory mismatches, these studies promoted the usage of PENs to label a perceived loss in physical immersion, potentially impacting presence experience thereby providing continuous diagnostics about user experience.…”
Section: Introductionmentioning
confidence: 99%